Quantitative Analysis of Factors Affecting the Optical Burst Switching Through Fuzzy Multi Criteria Decision Making AHP Technique - Gayatri Tiwari, Ram Chandra Singh Chauhan (International Journal of Advanced Science and Technology, 2020)
The exponential growth of internet now a day seems to be enhancing the optical network, which is used as backbone of internet. With the recent development of 5G technology the requirement of optical channel, switching technique and data transmission rate are important, our research aim is to focus on switching technique, Optical Burst Switching (OBS). OBS is also necessary for future development of communication network. The number of internet user increases exponentially as per recent development of bulk data transmission through the optical fiber network. OBS is the process of switching between electronic to optical networks. Here we have selected the five different switching methods asalternatives and five dependent factors which are based on switching.The different switching methodsand dependent factors were evaluated by the multi criteria decision methodology Fuzzy Analytic Hierarchy Process (FAHP). FAHP method is used to find out the weight and rank of the alternative. We analyze the switching alternatives with the help of methodology FAHP, the alternative optical circuit switchinghas highest satisfaction degree, and the factor void filling scheduling algorithm has lowest.These techniques are very useful for the developer to select the burst switching technique as per requirement, to reduce the effect of factor in different switching methods the developers select the best methods of switching as per requirements.